The Development of Participative Clinical Supervision Model among the Nursing Division in Naradhiwas Rajanagarindra Hospital - เมืองประเสิรฐ, ศิริวรรณ; คงคากุล, อุษณีย์; สะมาแอ, นริสา; ไข้บวช, ทัศณียา; เอี่ยมวุฒิวัฒนา, จุฑามาศ; เจริญวงศ์, สรวงสุดา (Princess of Naradhiwas University Journal, 2018)
This action research aimed to develop a participatory clinical supervision model for the nursing division at Narathiwat Rajanagarindra Hospital. Purposive sampling method was applied to select 25 supervisorsof nurse directors and head nurses, as well as 175 registered nurses. Qualitative data were collected byfocus group, observation, field notes and open-ended questionnaires about supervisory situations. Quantitative data were collected through questionnaires assessing satisfaction for nursing supervision. Data were analyzed by using content analysis and dependent t-test. The study revealed that the participatory clinical supervision model consisted of 12 planning items. Supervisors and supervisees should compromise and play role in all operating processes of the clinical supervision model. Supervisors should be confident in their knowledge and supervision skills. The positive perception of supervisees would improve nursing knowledge and promoted nursing skills. The satisfaction average scores toward nursing supervision of supervisors and supervisees after implementing the participatorymodel were significantly higher than before implementing the model (t=3.65, t=8.86, p-value <0.05, respectively). The key success factors were participatory process and promoting motivation.